A Study on the Effect of Irradiation Angle of Light on Defect Detection in Visual Inspection - Nakajima, Ryosuke; Shida, Keisuke; Matsumoto, Toshiyuki (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
This study focuses on the difference in the visibility of defects according to the irradiation angleof the light in visual inspection using fluorescent light, and also considersthe relationship between the irradiation angle and the defect detection. In the experiment, the irradiation angle of light is considered as the experimental factors. The visibility of defects that are different according to the irradiation angle of the light are reproduced using a tablet PC, and the effect of inspection movement on the defect detection is evaluated. As the result, it is observed that the inspection oversights occurs by the irradiation angle of light. Also, it is observed that the angle formed by the visual line and the inspection surface becomes not perpendicular, the defects detection also becomes more difficult. Based on the above observation, new inspection method is proposed instead of the conventional inspection method.